Species-specific pharmacology of maximakinin, an amphibian homologue of bradykinin: putative prodrug activity at the human B(2) receptor and peptidase resistance in rats - Charest-Morin, Xavier (PeerJ, 2017)
Maximakinin (MK), an amphibian peptide possessing the C-terminal sequence of bradykinin (BK), is a BK B(2) receptor (B(2)R) agonist eliciting prolonged signaling. We reinvestigated this 19-mer for species-specific pharmacologic profile, in vivo confirmation of resistance to inactivation by angiotensin converting enzyme (ACE), value as a module for the design of fusion proteins that bind to the B(2)R in mammalian species and potential activity as a histamine releaser. Competition of the binding of [(3)H]BK to recombinant human myc-B(2)Rs in cells that express these receptors revealed that MK possessed a tenuous fraction (<0.1%) of the affinity of BK, despite being only ∼20-fold less potent than BK in a contractility assay based on the human isolated umbilical vein. These findings are reconciled by the generation of C-terminal fragments, like Lys-Gly-Pro-BK and Gly-Pro-BK, when the latent MK is incubated with human venous tissue (LC-MS), supporting activation via hydrolysis upstream of the BK sequence. At the rat recombinant myc-B(2)R, MK had a lesser affinity than that of BK, but with a narrower margin (6.2-fold, radioligand binding competition). Accordingly, MK (10 nM) stimulated calcium transients in cells that expressed the rat receptors, but not the human B(2)R. Recombinant MRGPRX2, a receptor that mediates cationic peptide-induced mast cell secretion, minimally responded by increased [Ca(+2)](i) to MK at 10 µM. Enhanced green fluorescent protein fused to MK (EGFP-MK) labeled cells that expressed rat, but not human B(2)Rs. Intravenous MK induced dose-dependent hypotensive, vasodilator and tachycardic responses in anesthetized rats and the effects were antagonized by pretreatment with icatibant but not modified by pyrilamine or enalaprilat. Strong species-specific responses to the toxin-derived peptide MK and its prodrug status in the isolated human vein were evidenced. Accordingly, MK in the EGFP-MK fusion protein is a pharmacophore module that confers affinity for the rat B(2)R, but not for the human form of the B(2)R. MK is unlikely to be an efficient mast cell activator, but its resistance to inactivation by ACE was confirmed in vivo.